2016
DOI: 10.1021/acs.jpcc.5b11067
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Energy Transfer Process in Doped-Anthracene Nanoaggregates is Controlled by Exciton Diffusion: Multiple Doping Leads to Efficient White Light Emission

Abstract: Quite similar structures of polycyclic aromatic hydrocarbons make them suitable for doping of one molecule into the crystalline structure or aggregate of another and tuning of the optical properties of the composite system. Anthracene nanoaggregates, singly or multiply doped with perylene, tetracene, and pentacene, have been synthesized using reprecipitation technique. Following photoexcitation of anthracene molecule in the nanoaggregate, anthracene exciton transfers energy to the dopant molecule(s). Energy tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…However, it was also observed that reprecipitation of TIPS-Pn into dilute aqueous poly­(vinyl alcohol) (PVA) solutions induced an identical effect, and an additional study has since reported modulation of pyrene NP morphology using a similar method . PVA is a common additive in the preparation of both organic , and inorganic NP dispersions, although the rationale for its use is often unclear. Some authors have noted that inclusion of PVA appears to stabilize NP dispersions through binding to the surface and acting as a capping agent, , while others have also suggested that it influences the nucleation stage through controlling factors such as viscosity and surface tension .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also observed that reprecipitation of TIPS-Pn into dilute aqueous poly­(vinyl alcohol) (PVA) solutions induced an identical effect, and an additional study has since reported modulation of pyrene NP morphology using a similar method . PVA is a common additive in the preparation of both organic , and inorganic NP dispersions, although the rationale for its use is often unclear. Some authors have noted that inclusion of PVA appears to stabilize NP dispersions through binding to the surface and acting as a capping agent, , while others have also suggested that it influences the nucleation stage through controlling factors such as viscosity and surface tension .…”
mentioning
confidence: 99%
“…PVA is commonly used as a templating or emulsifying agent in the preparation of organic NP dispersions, typically acting as a capping agent to promote particle dispersity and minimize aggregation. ,,,,, Previous studies have shown that inclusion of PVA in the reprecipitation step slows the growth of perylene NPs and favors the formation of the crystalline phase in pyrene NPs . However, in all of these previous reports, PVA acts as a template to guide the formation of NPs to a desired size or morphology and is considered only within the context of NP formation and growth.…”
mentioning
confidence: 99%
“…The observed decays were analyzed with a suitable exponential function to obtain the best fits for the decays. Sub-ps time-resolved emission and transient absorption experiments were executed by using fluorescence up-conversion (FOG-100, CDP corporation, Russia) and ultrafast transient absorption (ExciPRO, CDP Corporation, Russia) spectrometers, respectively. , The above spectroscopic setups are coupled with an amplified ultrafast laser module obtained from Amplitude Technologies, France. The detailed elaboration of the above experimental setups are available in previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…67 The values for R a are 0.9 ± 0.21 and 1.49 ± 0.28 nm for peri and bay derivatives, respectively. Further, the values of the exciton diffusion coefficient and singlet exciton lifetime are used to estimate the exciton diffusion length (L D = √6Dτ), 70 which is nothing but the mean distance travelled by an exciton during its lifetime. These parameters are provided in Table 2 for both the compounds.…”
Section: Steady-state Absorption and Emission Studiesmentioning
confidence: 99%
“…The decaying emission of the naphthaleneimide skeleton may be explained in terms of an energy transfer from 3a to 4a. 11 Fig. S6 † shows the concentration-dependent emission spectra of 3a in CHCl 3 .…”
mentioning
confidence: 99%